"Getting out of downtown": a longitudinal study of how street-entrenched youth attempt to exit an inner city drug scene - Rod Knight; Danya Fast; Kora DeBeck; Jean Shoveller; Will Small (BMC, 2017)
Abstract Background Urban drug "scenes" have been identified as important risk environments that shape the health of street-entrenched youth. New knowledge is needed to inform policy and programing interventions to help reduce youths' drug scene involvement and related health risks. The aim of this study was to identify how young people envisioned exiting a local, inner-city drug scene in Vancouver, Canada, as well as the individual, social and structural factors that shaped their experiences. Methods Between 2008 and 2016, we draw on 150 semi-structured interviews with 75 street-entrenched youth. We also draw on data generated through ethnographic fieldwork conducted with a subgroup of 25 of these youth between. Results Youth described that, in order to successfully exit Vancouver's inner city drug scene, they would need to: (a) secure legitimate employment and/or obtain education or occupational training; (b) distance themselves - both physically and socially - from the urban drug scene; and (c) reduce their drug consumption. As youth attempted to leave the scene, most experienced substantial social and structural barriers (e.g., cycling in and out of jail, the need to access services that are centralized within a place that they are trying to avoid), in addition to managing complex individual health issues (e.g., substance dependence). Factors that increased youth's capacity to successfully exit the drug scene included access to various forms of social and cultural capital operating outside of the scene, including supportive networks of friends and/or family, as well as engagement with addiction treatment services (e.g., low-threshold access to methadone) to support cessation or reduction of harmful forms of drug consumption. Conclusions Policies and programming interventions that can facilitate young people's efforts to reduce engagement with Vancouver's inner-city drug scene are critically needed, including meaningful educational and/or occupational training opportunities, 'low threshold' addiction treatment services, as well as access to supportive housing outside of the scene.